1D alloy ultrafine Pt–Fe nanowires as efficient electrocatalysts for alcohol electrooxidation in alkaline media. Issue 35 (28th August 2018) - Song, Pingping; Xu, Hui; Wang, Jin; Zhang, Yangping; Gao, Fei; Guo, Jun; Shiraishi, Yukihide; Du, Yukou
Abstract : Ultrafine Pt–Fe Nanowires (NWs): Owing to anisotropy, high surface area and excellent conductivity of the ultrafine Pt–Fe NWs, they are more beneficial for the improvement of catalytic activity and stability enhancement compared with commercial Pt/C, thus opening a new way to promote fuel cell reactions. Abstract : Fuel cells have been gaining much interest due to their advantages of high energy conversion efficiency, easy handling, etc ., whereas some drawbacks of anode catalysts regarding limited performances have seriously restricted their practical applications. Therefore, the development of anode nanocatalysts with higher activity and stability has become an urgent need. In view of this, we have developed a facile wet-chemical approach to synthesize 1D alloy ultrafine Pt–Fe NWs, and we have also revealed the formation mechanism of the ultrafine Pt–Fe NWs using time-dependent studies. More importantly, 1D ultrafine nanowires with anisotropy, superior flexibility, high surface area and excellent conductivity are promising candidates for the improvement of nanocatalytic activity and stability enhancement. Therefore, the electrocatalytic activities of ultrafine Pt3 Fe NWs in the oxidation of ethylene glycol and glycerol are 3.9 and 2.5 times greater than that of commercial Pt/C, respectively. Moreover, they provide excellent long-term stability. Our efforts may potentially promote the commercialization of fuel cells to some extent.